Transformasi Pangan Lokal Dou Mbojo: Inovasi “Salome Bandeng” dan “Granola Moringa” sebagai Strategi Pencegahan Stunting Di Kabupaten Dompu - Andriani, Mardian; Mariamah; Muhammad; Yanti, Sri; Ihsan; Hairunis, Mirham Nurul; Fitriani, Ririn; Nabila, Putri; Rasidin, Aiman; Unem, Bilel; Sika; Sultan S, M.; Sahlan, Meilan; Imam, Takbil; Putra, M. Fadhil Mandala; Nurfadilah, Aulia; Ulva, Mariam; Sulvani; Rahmatulah, Sarif; Kaafah, Nursilmi; Juniati, Tri; Ferdiansyah, Aril (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
This PKM-BEM program aims to enhance nutrition literacy and skills in producing nutritious local food in Mbawi Village, Dompu Regency, through two innovative products: Salome Bandeng (milkfish sausage) and Granola Moringa. The implementation method involved socialization, food innovation training, and a digital marketing workshop engaging the local women’s group (PKK) and housewives. A total of 30 participants took part actively. The results showed a 45% increase in nutrition knowledge based on pre–post tests, an 80% improvement in production skills, and two active social media accounts (Instagram & Facebook) used for product promotion. Salome Bandeng and Granola Moringa were produced in approximately 100 packages and received a positive acceptance rate of 85%. This program successfully improved the community’s nutritional and economic capacity while encouraging the formation of the Pokja Pangan Lokal Sehat (Healthy Local Food Working Group) as the embryo of the Dou Mbojo Food microenterprise.